Potential alternative natural colourant from Dendrobium Sonia ‘Earsakul’ - Netramai S. (2023)
This study aimed to investigate optical properties, colour-changing characteristics, and storage stability of crude aqueous extract of fresh Dendrobium Sonia ‘Earsakul’ (DSE) orchid flower obtained through microwave-assisted extraction. IR spectra of the extract at various pH indicated that anthocyanins were major pigments present in the crude extract. As the pH of the extract increased from 2 to 11, its colour turned from reddish-orange to magenta to purple to blue to green. Crude extract of DSE could be prepared in advance and used within 2 weeks after preparation (if kept at 4°C) without significant reduction of anthocyanin levels (P<0.05). The findings showed that DSE had the potential to be utilized as a natural food colourant as an alternative for those from plants containing cyanidin as the major anthocyanin, due to their similarities in colour-changing patterns and high storage stability.